PHYSICAL LAYER SECURITY USING MASSIVE MIMO AND RIS TECHNOLOGY - Abdrakhmanov, Rakhat (Nazarbayev University School of Engineering and Digital Sciences, 2024)
Massive Multiple-Input-Multiple-Output (MIMO) systems and Reconfigurable Intellegent Surfaces (RIS) are considered to be the key technologies for next generations wireless communication, which are aimed to achieve higher data rates, massive connectivity and more secure data transmission. Combined use of these technologies together with artificial noise (AN) gives high hopes for strengthening Physical Layer Security (PLS) in wireless networks. This capstone work considers configuring phase shifts of RIS such that the impact of AN is maximized for illegitimate user, while its impact on legitimate user is not significant compared to the actual signal received from base station. In the proposed system model, some antennas is dedicated for AN and the rest are transmitting the actual data. The main objective of this model is to maximize Secrecy Capacity (SC) of the communication link, while satisfying the users’ quality of service (QoS). To achieve that, we optimize the phase shifts of RIS and find the optimal number of base station antennas transmitting AN. Obtained results validate theoretical concepts and show that proposed RIS-assisted Massive MIMO incorporated with AN transmission can be an effecting tool for establishing and improving PLS in wireless communication.
Keywords: MIMO; Type of access: Open access; RIS; 5G; Physical Layer Security; Wireless Communication; Data rate; Channel capacity; Signal to interference and noise ratio; Quality of service